2014
DOI: 10.1080/10916466.2011.611563
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reservoir Properties on Pseudo Functions: Upscaling of Relative Permeability

Abstract: Relative permeability is the most challenging parameter during the scale-up process. Dynamic pseudoization approaches are the best methods for upscaling of relative permeability. However, dynamic pseudo functions are dependent to some reservoir properties. In this study, the effects of absolute permeability, PVT properties, vertical to horizontal permeability ratio, and reservoir dip angle on three dynamic pseudo functions of Kyte and Berry, Stone, and transmissibility weight were investigated. Different reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Relative permeability measurements of hydrogen-water system in Berea sandstone, conducted by Lysyy et al [101], showed a significant effect of hysteresis on the curves of water and hydrogen relative permeability. Hashemi et al's [102] PNM results indicate that due to the disconnect of hydrogen phase after residual water and secondary imbibition in porous media, the relative permeability values of secondary drainage are lower than primary drainage. However, hysteresis effects remain unchanged with more cycle occurrences.…”
Section: The Impact Of Relative Permeability Hysteresis On Co 2 Seque...mentioning
confidence: 99%
“…Relative permeability measurements of hydrogen-water system in Berea sandstone, conducted by Lysyy et al [101], showed a significant effect of hysteresis on the curves of water and hydrogen relative permeability. Hashemi et al's [102] PNM results indicate that due to the disconnect of hydrogen phase after residual water and secondary imbibition in porous media, the relative permeability values of secondary drainage are lower than primary drainage. However, hysteresis effects remain unchanged with more cycle occurrences.…”
Section: The Impact Of Relative Permeability Hysteresis On Co 2 Seque...mentioning
confidence: 99%